2022
DOI: 10.1111/ajt.17126
|View full text |Cite
|
Sign up to set email alerts
|

Utilization and outcomes of deceased donor SARS-CoV-2–positive organs for solid organ transplantation in the United States

Abstract: Coronavirus disease‐19 has had a marked impact on the transplant population and processes of care for transplant centers and organ allocation. Several single‐center studies have reported successful utilization of deceased donors with positive severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) tests. Our aims were to characterize testing, organ utilization, and transplant outcomes with donor SARS‐CoV‐2 status in the United States. We used Scientific Registry of Transplant Recipients data from March 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
57
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(69 citation statements)
references
References 26 publications
5
57
1
2
Order By: Relevance
“…However, the use of extra‐pulmonary organs from the same donors has resulted in no clinical signs of donor‐derived SARS‐CoV‐2 and no reported ill‐ effects on allograft or patient outcomes 9,11 . Case reports, small case series and now recent summative OPTN data of liver, kidney and heart transplantation from donors with SARS‐CoV‐2 detection have been published with excellent recipient outcomes 12–25 . While the OPTN data is supportive of the safe use of organs from donors with SARS‐CoV‐2 detection, donor and recipient details that may illustrate the likelihood of active infection or infection‐related complications are lacking 25 …”
Section: Introductionmentioning
confidence: 99%
“…However, the use of extra‐pulmonary organs from the same donors has resulted in no clinical signs of donor‐derived SARS‐CoV‐2 and no reported ill‐ effects on allograft or patient outcomes 9,11 . Case reports, small case series and now recent summative OPTN data of liver, kidney and heart transplantation from donors with SARS‐CoV‐2 detection have been published with excellent recipient outcomes 12–25 . While the OPTN data is supportive of the safe use of organs from donors with SARS‐CoV‐2 detection, donor and recipient details that may illustrate the likelihood of active infection or infection‐related complications are lacking 25 …”
Section: Introductionmentioning
confidence: 99%
“…The results of KEGG and GO pathway enrichment indicated that those genes were mostly enriched in DNA replication, immunomodulation, and energy metabolism. Increasing studies of COVID-19 patients showed that SARS-Cov-2 infects and replicates in endothelial cells in multiple organs, such as the heart, lung, kidney, and liver ( Dashtban et al, 2022 ; Giovannini et al, 2022 ; John et al, 2022 ; Kumar et al, 2022 ; Schold et al, 2022 ; Zheng et al, 2022 ). In addition, the enriched pathway p53 signaling was identified as a key pathway of genomic stability and cell cycle progression, it even plays a great part in the suppression of viral replication ( Kumar et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, to date, there have been no reports of recognized transmissions of SARS-CoV-2 following blood transfusion, even in immunosuppressed patients [ 196 , 197 ]. Therefore, although, the number of transplants reported from positive SARS-CoV-2 donors is still relatively small, there is no clear evidence of additional risk to allograft survival [ 198 ].…”
Section: Covid-19 In Patients With Pre-existing Chronic Liver Diseasementioning
confidence: 99%